2005
DOI: 10.1103/physrevlett.95.226101
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Phonon Thermal Transport in Multiwalled Carbon Nanotubes

Abstract: We report electrical transport experiments, using the phenomenon of electrical breakdown to perform thermometry, that probe the thermal properties of individual multiwalled carbon nanotubes. Our results show that nanotubes can readily conduct heat by ballistic phonon propagation. We determine the thermal conductance quantum, the ultimate limit to thermal conductance for a single phonon channel, and find good agreement with theoretical calculations. Moreover, our results suggest a breakdown mechanism of thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
123
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 27 publications
(46 reference statements)
16
123
1
2
Order By: Relevance
“…[1][2][3] Of particular interest are carbon nanotubes, which have been proposed both as prototypical nanoscale circuit elements and by, virtue of their extraordinary current carrying capacity, as potential materials for interconnects. Recent studies have shown that nanotubes are remarkable thermal conductors [4][5][6][7][8] even at elevated temperatures 9,10 and ballistic phonon transport has been demonstrated in micron-scale devices, [11][12][13] with a mean free path in agreement to theoretical calculations. 14 Nevertheless, for thermal management it is also of interest to determine the thermal resistance between nanotubes and different materials.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…[1][2][3] Of particular interest are carbon nanotubes, which have been proposed both as prototypical nanoscale circuit elements and by, virtue of their extraordinary current carrying capacity, as potential materials for interconnects. Recent studies have shown that nanotubes are remarkable thermal conductors [4][5][6][7][8] even at elevated temperatures 9,10 and ballistic phonon transport has been demonstrated in micron-scale devices, [11][12][13] with a mean free path in agreement to theoretical calculations. 14 Nevertheless, for thermal management it is also of interest to determine the thermal resistance between nanotubes and different materials.…”
supporting
confidence: 50%
“…However, these phonons are expected to decay into the thermal population before they can carry significant thermal energy out of the nanotube. 11 Figure voltages because of the increased scattering from optical or zone boundary phonon emission, tending towards the maximum of 4e / hE op-zb Ϸ 25 A/nanotube shell, where E op-zb ϳ 0.18 eV is the characteristic zone boundary or optical phonon energy in nanotubes. 21 Although the maximum current can vary for each device, the required power to reach breakdown increases approximately linearly with the nanotube length.…”
mentioning
confidence: 99%
“…Similar results have also been observed for individual NTs. 4,11,13 The rapid increase of current with voltage has also been observed for experiments performed at different pressures (10 -6 Torr range) as shown in Figs. 2(b)-2(d).…”
Section: Resultsmentioning
confidence: 55%
“…9,10 Not only in the ballistic regime, but also the absence of current saturation has been reported in the diffusive regime. 4,[12][13][14] It may also be noted that IV characteristics reported in Refs. 6, 11 is different from that reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation